Analysis and comparison of influence factors of hot water temperature in transcritical CO2 heat pump water heater: An experimental study. (15th October 2019) - Yang, Lingxiao; Qin, Xiang; Zhao, Linghua; Ye, Song; Wei, Xinli; Zhang, Dongwei
Highlights: A new indicator named unit temperature-lift cost (UTC) has been proposed. The water-inlet flowrate has the best effects of rising hot water temperature. Controlling water-inlet temperature is unadvisable to lift hot water temperature. Abstract: In order to investigate the factors that affect the hot water outlet temperature on air-source transcritical CO2 heat pump water heater, an experimental research is designed where the expansion valve opening is controlled to adjust the discharge pressure. The experiments are conducted at different compressor speeds, water-inlet flowrates and water-inlet temperatures. Then, a new indicator named unit temperature-lift cost (UTC) is proposed to evaluate the lifting effects of hot water temperature. The results show that the rise of hot water temperature leads to the decrease of the maximum coefficient of performance (COP) but the increase in both the gas-cooler outlet temperature at the optimal status and the optimal discharge pressure, which are mainly caused by the variations of gas-cooler outlet status. At ranges of compressor speeds, water-inlet flowrates and water-inlet temperatures, the UTCs always show a drop with a higher required hot water temperature, and the corresponding average UTCs are 0.054 °C −1, 0.042 °C −1 and 0.099 °C −1, respectively. According to the results, the method of controlling the water inlet flowrate should be taken as a priority to lift the hot water temperature of the system. The compressor speed is suitable to meet the needs of increasing hot water temperature and heating capacity simultaneously. It is not advisable to increase the hot water temperature by adjusting the water inlet temperature.